Parametrix method for a parabolic equation on a Riemannian manifold - Bondarenko, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We present a scheme of construction of a fundamental solution of a parabolic equation on a Riemannian manifold with nonpositive curvature.